The Influence of Work Discipline and Compensation on Teacher Achievement Working at Northtern Green School Medan - Irwadi; Andriaskiton, Mario; Buulolo, Yusminta (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of conducting this research or scientific work is to find out the work performance of teachers at the Northern Green School which is influenced by the variables of work discipline and compensation. This research was then designed using a quantitative descriptive research methodology. To be able to determine the relationship between two or more variables can be done using a quantitative descriptive research method. When conducting quantitative descriptive research, questionnaires containing various question items were distributed to participants or respondents in related research. Furthermore, it can be ascertained that the questions in the questionnaire are definitely related to the research variables used in the study. The findings from this study showed that there was a positive and significant relationship between the variables of work discipline and compensation and teacher achievement at the Northern Green School.